Tafsir Tarbawi dan Maudlu'i Dalam Pendidikan Islam: Surah Al-Ghāshiyah Dan Luqman - Mufti Labib (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2026)
Contemporary Islamic education faces challenges in integrating the transcendental values of the Qur’an with modern pedagogical demands. This article examines Sura Al-Ghāshiyah and Sura Luqmān through an integrative approach combining tafsir tarbawi and tafsir maudlu‘i to formulate a holistic framework for Islamic education. This study employs a qualitative method based on library research and content analysis of Qur’anic texts as well as classical and contemporary exegetical literature. The tafsir maudlu‘i approach is used to identify educational themes based on thematic unity (al-wahdah al-maudlu‘iyyah), while tafsir tarbawi is applied to analyze educational objectives, methods, and pedagogical implications derived from the two surahs. The findings indicate that Sura Al-Ghāshiyah emphasizes eschatological awareness and rational faith development through reflective engagement with nature (tafakkur al-kawni) and a non-coercive educational approach. Meanwhile, Sura Luqmān presents a family-based educational model grounded in dialogical instruction (maw‘izhah ḥasanah), exemplary conduct (uswah ḥasanah), and gradual character formation. The integration of these two surahs generates a holistic paradigm of Islamic education that harmonizes transcendental (afterlife awareness), rational (critical thinking), and ethical (character formation) dimensions. This model contributes to the development of Islamic education curricula oriented not only toward knowledge transmission but also toward consciousness transformation and the formation of a well-rounded Muslim personality. The study enriches the discourse on Qur’anic educational exegesis and offers a contextual and applicative methodological alternative for the development of revelation-based Islamic education.